Towards a systematic framework to assess restoration success of interventions in coral reef ecosystems - Aldo Croquer; Sergio D. Guendulain-García; Jonathan S. Lefcheck; Leah Harper; Elizabeth Shaver; Rita I. Sellares-Blasco; Maria F. Villapando; Ainhoa L. Zubillaga; Rebecca Garcia-Camps; Andreina Rivera; Eva Salas; Jennifer Humberstone; et al. (PLoS ONE, 2026)
An ecosystem is defined as a collection of organisms that move energy within and outside of a system, while sustaining both the system itself and the multiple services that benefit humanity. Ecosystem restoration, then, is ultimately concerned with reviving and maintaining ecosystem processes by repopulating organisms and enhancing the habitat after periods of disturbance or loss. Whether interventions are considered “successful” depends on three criteria: 1) were the goals/outcomes clearly defined before implementing the intervention; 2) did the outcome arise directly from the intervention, and 3) does the outcome reflect a functioning ecosystem in the long term (e.g., > 10 years)? The answers to these questions have been challenging for coral restoration practitioners, as they are often hindered by the lack of predefined hypotheses and rigorous experimental design and by confusion between metrics quantifying coral production and outplanting efforts rather than recovery of community structure and ecosystem functioning. As a result, the impacts of restoration efforts are inconsistently and often incorrectly interpreted, and funding is often tied to intervention activities instead of outcomes. Here, we present a framework to implementing robust experimental designs and measure more relevant ecosystem indicators in order to assess the impacts of interventions and promote more informed and effective restoration outcomes. We then illustrate these concepts by reviewing coral restoration-specific case studies to demonstrate the degree to which successful outcomes under such a framework have been achieved. Through these practical recommendations, we hope to support coral restoration practitioners in designing and executing future interventions, and to encourage the broader community, including funders, to adopt a more systematic framework to evaluate and report restoration success.